Características clínico-laboratoriais, análise mutacional do gene PIG-A e perfil metabolômico em pacientes com hemoglobinúria paroxística noturna - Yamakawa, Patricia Eiko [UNIFESP] (2019)
Introduction: Paroxysmal nocturnal hemoglobinuria (PNH) is a disorder due to an acquired abnormality in the phosphatidylinositol glycan class A (PIG-A) gene. This leads to partial or complete absence of all GPI-linked proteins, like the complement regulatory proteins CD59 and CD55, resulting in an increased sensitivity of the red blood cells to the action of complement. The clinical manifestations of PNH include hemolytic anemia, a hypercoagulable state, and reduced hematopoiesis. Aims: 1) To study the clinical characteristics of a group of patients with classical PNH, PNH associated with another bone marrow disorder or subclinical PNH (PNH clone associated with another bone marrow disease); 2) To identify and to correlate PIG-A gene mutations with clinical manifestations in these groups of patients; 3) To compare a metabolomic profile in the hemolytic group with healthy controls, and 4) To compare a metabolomic profile before and after the use of eculizumab. Patients and methods: We studied 109 patients with PNH clone: 56 had hemolytic PNH (44 classical PNH and 12 associated with other bone marrow disorder), and 53 patients had subclinical PNH - PNH clone (defined as at least 0.01% of cells with PNH clone) associated with another bone marrow disease (aplastic anemia in 95% of the cases). The sequencing of the PIG-A gene was performed in 31 patients using the Sanger technique. To perform metabolomic profile, we used mass spectrometry (Kit AbsoluteIDQ p180, Biocrates, Austria) in 23 patients with hemolytic PNH. Besides, in twelve patients samples were also collected before and 24 hours after receiving eculizumab. The statistical analysis was performed by the software MetaboAnalyst 4.0. Results: Among the 109 patients included, 51% were male, the median age at diagnosis was 41 years, ranging from 18 to 81. Among the patients with hemolytic PNH, 86% had fatigue, 66% had hemoglobinuria, 45% abdominal pain and 16% had dysphagia. Venous thromboembolism was observed in 14 cases (25%), with abdominal thrombosis in 7 cases (50%). Seven patients (13%) had arterial thrombosis (stroke or transient ischemic attack). Among the 31 patients analyzed for PIG-A mutations, 29 different variations were detected in 27 patients: 23 were new mutations, with no previous description in the literature, 3 were previously described mutations and 3 were single nucleotide polymorphism. Mutations were predominantly small deletions and simple base changes. There was no correlation between the PIG-A mutations and the clinical manifestations. The major metabolites increased in the PNH group were long- chain acylcarnitines, while the major metabolites reduced in the PNH group were phosphatidylcholines, histidine, glutamate, taurine and aspartate. The C14:1/C16:1 ratio was shown to be a reliable marker in these patients with PNH, suggesting a disorder in lipid elongation. When we evaluated patients immediately before and 24 hours after receiving eculizumab, we noticed a trend toward normalization at C6:1 dosage and C14:1/C6 and C4/C6 ratios. Conclusions: We observed that the clinical characteristics and the distribution of the three subtypes of PNH in this study were similar to other published series, except for relatively lower rates of thrombosis, chronic kidney disease and mortality. PIG-A mutations were detected in the majority of patients with PNH, and almost all (except three) were novel. No correlation was observed between mutation types and clinical manifestation. We found differences in the metabolites of PNH patients when compared to healthy controls, suggesting a different metabolic profile of these patients, returning to normal levels with the use of eculizumab.